Partisipasi Masyarakat dalam Pengelolaan Desa Sampah Mandiri di Desa Kalisoro, Tawangmangu, Kabupaten Karanganyar - Chintami Dian Balenina (BESTUUR, 2019)
Kalisoro urban village is one of the tourism areas faced with the problem of increasing garbage pile and the absence of awareness of the waste. This problem really needs more attention especially in waste management. In this waste management is needed the help of participation from society. Waste management in Kalisoro Village is an independent waste management village that involves the society. In this management using the 3R method of Reuse, Reduce, and Recycle. This study aims to describe the participation of independent waste village management by describing the stages of participation society, the level of participation society, and the factors that influence community participation. This research is presented in qualitative descriptive form, using in-depth interview technique in data collection and also using data triangulation technique with interactive data analysis technique. In this research, the result of participation society in the management of the independent waste villages is managed by the community represented by the Non-Governmental Groups. Forms of participation society is to contribute ideas, energy, funds, and participate in waste collection. However, not all communities in Kalisoro Village participated directly. The level of participation society in Kalisoro Village includes Citizen Power. Keywords: Participation Society , Management of Waste.